2010
DOI: 10.21432/t2b01g
|View full text |Cite
|
Sign up to set email alerts
|

Using Videoconferencing to Provide Mentorship in Inquiry-Based Urban and Rural Secondary Classrooms

Abstract: The main purpose of this design-based research study is to examine the effects of an inquiry-based learning environment, with the support of videoconferencing, on both rural and urban secondary students’ mathematics and science learning. An important aspect of this learning environment is the use of videoconferencing to connect classes with mathematicians/ scientists (as e-mentors). Specifically, the following two research questions guide this study: (1) In what ways, if any, does the inquiry-based learning en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Nevertheless, studies have shown that some students may dislike the PbL approach (Brickman, Gormally, Armstrong, and Hallar, 2002;Mohamed, 2008;Li, Dyjur, Nicolson, and Moormann, 2009). These studies report that students tend to frustrate themselves because they are engaged in activities that challenge them more than a traditional lecture session.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, studies have shown that some students may dislike the PbL approach (Brickman, Gormally, Armstrong, and Hallar, 2002;Mohamed, 2008;Li, Dyjur, Nicolson, and Moormann, 2009). These studies report that students tend to frustrate themselves because they are engaged in activities that challenge them more than a traditional lecture session.…”
Section: Related Workmentioning
confidence: 99%